การวิเคราะห์อภิมานงานวิจัยเฉพาะรายของผลการพัฒนาพฤติกรรมของเด็ก : การวิเคราะห์เปรียบเทียบการประมาณค่าขนาดอิทธิพล 3 วิธี - ภิรดี วัชรสินธุ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
Three purposes of this research were 1) to study the effect sizes of children s behavior development from 3 estimating methods, namely: estimation from standardized differences, estimation from percent of nonoverlapping data and estimation from regression analysis, 2) to synthesize the body of knowledge from the explanation of variances in effect sizes of children behavior development under different conditions based on research characteristics, and 3) to compare the meta-analysis results of single-subject research among 3 methods of effect size estimation. The research reports that were used for this synthesis were 99 single-subject research employing experimental design, from Chulalongkorn, Srinakharinwirot and Kasetsarl Universities. Data for this research consisted of 4,170 values of 3 effect sizes estimators and 40 variables pertaining to research characteristics. Descriptive statistics, analysis of variance, regression analysis, HLM and LISREL analyses were employed for data analysis. The results of research synthesis were: 1. The effect sizes of children behavior development from 3 estimating methods were, in average, 3.332,78.513% and 0.893. 2. Variables pertaining to research characteristics that were moderator variables accounting for differences in all the three methods of effect size estimators, were type of dependent variables, type of experimental group, age of sample, time at base-line period, and reliability of dependent variable. The research study treatment in social learning theory (4.04) and study dependent variables in emotional behavior (13.57) yielded high effect size. 3. Research characteristic variables could significantly account for 37.9 and 23.4 percents of variances in the first two methods of estimating effect size, but could not significantly explain variance in effect size estimating from regression analysis. 4. The comparisons of three estimating methods of effect size indicated that the standardized difference estimation and the regression analysis estimation were correlated. All methods had some limitations. The standardized difference estimation yielded extreme and overestimators. The percent of non-overlapping data estimation yielded many floor and ceiling values. The regression analysis estimation had complicated computation process.